PENGARUH ALMA TERHADAP KINERJA KEUANGAN DAN NILAI PERUSAHAAN PADA BANK YANG TERDAFTAR DI BURSA EFEK INDONESIA - DM, Rustan (LP2M Institut Teknologi dan Bisnis Asia Malang, 2020)
This study aims to determine the effect of ALMA on financial performance with Entity Value as an intervening variable. This type of research used a descriptive approach and explanatory approach, with exogenous variables namely ALMA and endogenous variables are financial performance and firm value. This study takes the population of all publicly listed banks listed on the IDX, as many as 37 (thirty seven) banks. In determining the sample, a purposive sampling technique was used. This study found that ALMA had a negative effect on company performance. ALMA has an indirect effect on firm value, company performance has an indirect effect on company value, ALMA through Company Performance has an indirect and significant effect on company value on several banks listed on the Indonesia Stock Exchange. The optimal application of ALMA enables all series of banking activities to be effective, efficient and effective.